2020
DOI: 10.1093/ntr/ntaa069
|View full text |Cite
|
Sign up to set email alerts
|

Timing- and Dose-Specific Associations of Prenatal Smoke Exposure With Newborn DNA Methylation

Abstract: Introduction Fetal changes in DNA methylation may underlie associations of maternal smoking during pregnancy with adverse outcomes in children. We examined critical periods and doses of maternal smoking during pregnancy in relation to newborn DNA methylation, and associations of paternal smoking with newborn DNA methylation. Aims and Methods This study was embedded in the Generation R Study, a population-based prospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Whereas a dose–response relationship was underlined by several studies (the more pregnant women smoked, the greater were changes in DNA methylation) [ 86 , 103 ], a recent study suggests that any exposure to tobacco smoke during pregnancy could be harmful toward infant lung function [ 99 ]. Monasso et al [ 86 ] and Rousseaux et al [ 97 ] explored different timing of exposure around pregnancy.…”
Section: Description Of Epigenetic Regulation Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas a dose–response relationship was underlined by several studies (the more pregnant women smoked, the greater were changes in DNA methylation) [ 86 , 103 ], a recent study suggests that any exposure to tobacco smoke during pregnancy could be harmful toward infant lung function [ 99 ]. Monasso et al [ 86 ] and Rousseaux et al [ 97 ] explored different timing of exposure around pregnancy.…”
Section: Description Of Epigenetic Regulation Mechanismsmentioning
confidence: 99%
“…Whereas a dose–response relationship was underlined by several studies (the more pregnant women smoked, the greater were changes in DNA methylation) [ 86 , 103 ], a recent study suggests that any exposure to tobacco smoke during pregnancy could be harmful toward infant lung function [ 99 ]. Monasso et al [ 86 ] and Rousseaux et al [ 97 ] explored different timing of exposure around pregnancy. In cord blood, Monasso et al identified 1391 CpGs differentially methylated in sustained (but not in women quitting smoking prior or in early pregnancy) vs. never smokers, among 5915 CpGs established with robust evidence for association with sustained maternal smoking in a prior meta-analysis [ 76 ].…”
Section: Description Of Epigenetic Regulation Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these changes persisted at 7 years and 17 years of age in offspring [ 50 ]. A study from the Generation R cohort found that changes in cord blood DNAm at 1391 CpGs was related to continued maternal smoking during pregnancy, whereas quitting smoking early in pregnancy and paternal smoking were not associated with DNAm changes at 5915 CpGs known to be related to maternal smoking [ 51 ].…”
Section: Dnam As a Potential Epigenetic Mechanism Linking Smoke Exposure Or Prenatal Stress To Childhood Respiratory Health Outcomesmentioning
confidence: 99%